Macroalgae diversity and its relationship with environmental conditions in polluted waters of Seribu Islands, Jakarta Bay, Indonesia - SRI HANDAYANI; IMAM WIDHIONO; DWI SUNU WIDYARTINI (Society for Indonesian Biodiversity, 2023)
Abstract. Handayani S, Widhiono I, Widyartini DS. 2023. Macroalgae diversity and its relationship with environmental conditions in polluted waters of Seribu Islands, Jakarta Bay, Indonesia. Biodiversitas 24: 6291-6298. Macroalgae are one of the important marine primary producers because they support the life of other organisms at a higher trophic level in aquatic ecosystems. This study aimed to determine the species diversity and composition of macroalgae and its relationship with local aquatic environmental conditions. This research was conducted in Seribu Islands, Jakarta Bay, and consisted of Pramuka Island, Semak Daun Island, Kotok Besar Island, Karang Bongkok Island, Kongsi Island, and Pari Island as sampling sites. This research used the transect method with quadratic sampling and the data was analyzed using the Shannon-Wiener Diversity Index, Dominance Index, and Evenness. Diversity parameter calculations were carried out using PAST4.0 software. The relationship between diversity and water quality was analyzed using PCA software. Across the six sampling sites, there were 41 species of macroalgae belonging to 3 divisions, namely Chlorophyta (19 species), Phaeophyta/Ochrophyta (10 species), and Rhodophyta (12 species). The species richness among islands showed that Karang Bongkok Island had the highest species with 28 species and the lowest was Semak Daun Island and Kongsi Island with only 15 species. The Diversity Index was the highest in Karang Bongkok Island with 2.679 and the lowest was in Kongsi Island with 1.907. The species with the largest number of individuals were Halimeda macroloba with 930 individuals, followed by Sargassum binderi with 648 individuals, and Corallina officinalis. with 257 individuals. The diversity of macroalgae species on the six islands is classified as moderate and can be used as an indicator of marine ecosystems. Physicochemical parameters that affect macroalgae diversity in the Seribu Islands waters are temperature, depth, currents, salinity, Total Dissolved Solids (TDS), pH, Dissolved Oxygen (DO), Cu, and Phosphate. The finding of this study implies that despite the high pollution in Seribu Islands waters, it is still good for the growth of macroalgae.